2007
DOI: 10.1155/2008/707864
|View full text |Cite
|
Sign up to set email alerts
|

Circulating VEGF As a Biological Marker in Patients with Rheumatoid Arthritis? Preanalytical and Biological Variability in Healthy Persons and in Patients

Abstract: Background: Soluble vascular endothelial growth factor (VEGF) is a promising biomarker in monitoring rheumatoid arthritis (RA), but studies of pre-analytical and biologic variability are few. Methods: VEGF was measured by ELISA methods in serum and plasma from healthy persons and RA patients. Pre-analytical factors were investigated. A reference interval for VEGF was established in serum and plasma from 306 healthy persons. Diurnal, day-to-day, week-to-week, long-term variability, and impact of exercise were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 21 publications
5
71
0
2
Order By: Relevance
“…In biobanking and longitudinal studies, samples are collected over time, stored freezers (−20 or −80 ℃), and then simultaneously analyzed in order to minimize inter-assay variability (209,210). However, as described in this article, the biomarkers are subject to variability arising from sampling and storage procedures (169). Erroneous sampling or handling and improper storage may lead to degradation of these markers, limiting their clinical reliability (211).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In biobanking and longitudinal studies, samples are collected over time, stored freezers (−20 or −80 ℃), and then simultaneously analyzed in order to minimize inter-assay variability (209,210). However, as described in this article, the biomarkers are subject to variability arising from sampling and storage procedures (169). Erroneous sampling or handling and improper storage may lead to degradation of these markers, limiting their clinical reliability (211).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, VEGF concentrations increased by 15% in both matrices (108). Similarly, Hetland et al found that up to ten freeze/thaw cycles of serum and EDTA-plasma samples from patients with RA, after 2 years of storage at −80 ℃, had no effects on VEGF immunoreactivity (169). These findings were in contrast with previous observations by Kisand and colleagues who showed that VEGF is very sensible to freeze/thaw: 67% decrease already after the first cycle.…”
Section: Pre-analytical Factorsmentioning
confidence: 94%
See 3 more Smart Citations